For Better of for Worse: The Statutory Derivative Action in Singapore - KOH, Pearlie (Institutional Knowledge at Singapore Management University, 1995)
Managerial accountability (or the lack of it) to shareholders has been described as “one of the major socio-legal problems of the twentieth century”. That such a comment has come to be made seems inevitable given the fact that common law courts have consistently upheld, in the absence of fraud, the managerial authority of the Board against the shareholders in general meeting. The Directors have almost absolute authority to decide what is, in their opinion, in the commercial interests of the company. The concerns of shareholders are obvious in public companies where, for the sake of economic efficiency and as a result of the development of the large public company as a capitalist venture, a divorce occurs between the specialist management and the owners/investors. But the problem cannot be said to be non-existent in smaller private companies. On the contrary, the position of the private minority shareholder could even be said to be worse. Here, the individual minority shareholder is concerned not only with managerial accountability but also with majority shareholder accountability. Unfortunately, the task of the single concerned shareholder, in his noble quest to ferret out corporate wrongdoing, whether committed by the elected directors or his fellow shareholders, has never been a bed of roses. He has faced monumental procedural obstacles when the wrong is classified, not as a wrong to him personally, but as a wrong to the corporation. Although technically, a wrong to the company is a wrong that should affect all shareholders alike, the problem is usually couched as one the minority shareholder has to bear, as some possibility of redress lies with the majority in general meeting.